VARIABILITY OF YIELD TRAITS IN A GERMOPLASM OF BARLEY CULTIVARS, STUDIED AT TURDA AGRICULTURAL RESEARCH AND DEVELOPMENT STATION, CLUJ COUNTY, ROMANIA - Emilia-Ancuța BOANTA; Leon MUNTEAN; Florin RUSSU; Ioana PORUMB; Raluca-Maria PARLICI; Andreea-Daniela ONA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Barley (Hordeum vulgare) is one of the essential cereal crops for humankind, the harvested area with barley ranks the 3rd place regarding grains cereals, after wheat and rice. The yield potential of barley, trait with complex genetic determinism, represents the maximum level of biomass which a genotype can realize under optimal conditions of growth and development as well as in an environment free of diseases, pests and weeds. The inheritance of quantitative traits involves a large number of genes which act additively in determining the character. To increase the yield potential of barley varieties, the present paper studied three traits which are involved in yield: spike length, grain weight/spike and grain number/spike that on 22 cultivars of barley, in ecological condition of ARDS Turda. Significance of the sample F for the genetic factor and interaction between the year and the genotype, for all three studied traits, reflects the fact that between those the 22 distinct genotypes there are very significant differences, which can be used in breeding programmes. As genitors for breeding programmes we can use cultivars Daciana, Romaniţa and To 2170/01 for spike lenght, cultivars Turdeana, Aura, Daciana and Xanadou for grain weight/spike and cultivars Turdeana and Adina for grain number/spike. The correlations between the three studied traits, which influence the barley yield, were positive, statistically assured, allowing their simultaneous improvement in the breeding programs.